Reawakening Ancestors, Gods and Spirits: An Investigation into Reconfigurations of “Sacred Space” in the Red River Delta of Northern Vietnam - Hoang, Chung Van (Material religion, 2023)
Since the onset of the Renovation Era in the late-1980s in Vietnam, a significant amount of resources and communal energy—both at the state and grassroots level—have been mobilized for the reconfiguration of communal spaces dedicated to worshiping ancestors, gods, and spirits. But by what precise means and in pursuit of what objectives has such sociocultural action taken place? Further, what are the long-term implications for state and society of these dynamic transformational processes that appear to be the norm in the contemporary era? This article seeks to address these and related questions by analyzing recently observed patterns of sociocultural action at communal "sacred spaces" dedicated to various forms of folk religion in the Red River Delta region of northern Vietnam. The authors argue that a process of “reconfiguration” is underway, which is characterized by a common pattern of practices and interventions that are physically and spiritually reshaping the region’s sacred space, including a set of prominent actors with highly particular motivations that guide their role in religious revival.